PHYTOCHEMICAL STUDY ON ECTOMYCORRHIZAL FUNGI Cortinarius Magellanicus: AN UNUSUAL BROMINATED SECONDARY METABOLITE ISOLATED - Bacho, Mitchell; Cajas, Daniel; Becerra, José; Fajardo Morales, Victor Manuel; San Martin Barrientos, Aurelio Del Carmen (My University, 2022)
Phytochemical analysis of the basidiomycete Cortinarius magellanicus (family Cortinariaceae) resulted in the isolation of eight secondary metabolites, where a brominated secondary metabolite was isolated for first time from a natural source. The structure elucidation of this compound was made using one- and two-dimensional NMR experiments, FT-IR, GC-MS, HRESIMS and chemical derivation. The disk diffusion assay of the brominated compound 4 and 8 revealed a low inhibition on Gram-positive and Gram-negative bacteria, respectively. No antifungal activities were detected for these compounds.
Keywords: brominated saccharide; cortinarius magellanicus; metabolite characterization; nothofagus ectomycorrhizal fungi; phytochemical analysis